Population and genomic variation of immune genes in chicken - Downing, Tim (Trinity College (Dublin, Ireland). Department of Genetics, 2010)
Achieving an understanding of the processes shaping diversity at chicken immune genes illuminates their population history, relevance to disease and mechanisms of evolution. Functional variation at genes that determine the resistance and susceptibility of chickens to infectious diseases can be identified by a combination of genomic surveys of variability and sequencing in diverse populations of modem birds. In this context, the work presented here describes the design and implementation of population and evolutionary genetic tests used to analyse the myriad effects of demographic history, pathogen-driven selection and functional constraint in the chicken immunome.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin.